The Legislative Shortcomings Aspects in the Jordanian Environmental Law. Comparison with International Law - EMAR, Omar; ABU ISSA, Hamzeh (Journal of Environmental Management and Tourism, 2021)
Most of the legislation in the countries have established laws and regulations to protect the national environment of countries, as Jordan is one of these countries, where the Jordanian environmental law has developed rapidly in order to keep pace with developments in various industrial and technological fields, for the purpose of protecting the environment and in cooperation with the relevant international and regional bodies, however, legal protection of the environment is not provided for in the text of the Constitution, also, the Jordanian legislator did not set up a special system for environmental damage compensation, did not included it in the civil law, in addition to the fact that local environmental legislation does not include the modern principles of environmental damage compensation contained in the international conventions, which signed and ratified by Jordan. The accumulation of these deficiencies affected the effectiveness of environmental law and the mechanism of its application.